Fluktuasi Bahan Organik dan Residu Terlarut dalam Budidaya Ikan Koi di Tulungagung, Jawa Timur - Al zamzami, Ilham Misbakudin; Sari, Alfi Hermawati Waskita; Perwira, Ima Yudha (Current Trends in Aquatic Science, 2019)
Water quality management is an important factor in the process of koi fish cultivation in the Minapolitan area, Tulungagung Regency. The purpose of this study was to observe the factual conditions of media water quality during maintenance using standard operational procedures in the water quality management process for koi fish maintenance media. This research was conducted on koi fish maintenance activities for 4 months. The maintenance process is carried out on 3 ponds with a total volume of 130,000 liters, and the amount of koi is 700 fish / pond. The process of feeding fish is done twice (morning and evening) with the amount of 3% of the weight of the fish. The composition of feed given during the maintenance process are: 38% protein, 5% fat, 3% fiber, 12% ash, and 11% moisture level. After measuring water quality, DO values ??did not differ greatly from 5.5 to 6.9 ppm. The range of EC values ??is 574-658 µS / cm, while the pH value is 7.7-8.9. The BOT values ??increase gradually with values ??of 2.6 ppm, 5.1 ppm, 12.7 ppm. The TDS value experienced an increase in the second month and tended to be stagnant at the 4th month with a value of 231 ppm, 287 ppm, 285 ppm. The data that has been collected is analyzed descriptively by comparing the increase in BOT and TDS lanes to see the water saturation limit, visualized in the form of line graphs.